DEVELOPING QUALITATIVE INSTRUMENT TO MEASURE ENTREPRENEUR KNOWLEDGE - Damelina Basauli Tambunan; Norashidah Binti Hashim (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
This study aims to produce a qualitative instrument for entrepreneur knowledge. Based on previous research, it was prepared a set of questions to determine the items that make up the entrepreneurial knowledge. Ten informants involved, they are all the entrepreneur. They were asked their opinions regarding the knowledge they need in running a business. The focus group discussion conducted to find the data. The results showed that there are four dimensions of knowledge entrepreneurs namely the level of education with three items statements, functional knowledge with ten items of the statement, the skill with nine items statement and the last is self-confidence with four items statement.